Dissecting Xuesaitong's mechanisms on preventing stroke based on the microarray and connectivity map1. Issue 11 (13th November 2015) - Wang, Linli; Yu, Yunru; Yang, Jihong; Zhao, Xiaoping; Li, Zheng
<x xml:space="preserve">Abstract</x> Dissecting the mode of action of Xuesaitong injection on preventing cerebral ischemia–reperfusion injury based on the combination of gene expression data analysis and the connectivity map.